The impact of initial group characteristics on quality in online communities of creation - Amira Rezgui; Kevin Crowston; Nicolas Jullien (2019)
Open projects aimed at creating new knowledge (also known as online communities of creation) are increasingly central in the production of new and innovative knowledge. In our research study, we are interested in the impact of initial group characteristics on the quality of the output. We studied in particular Wikipedia in different three languages: Arabic, Romanian and Thai. Our results confirm the importance of the initial project group. We found a positive impact of a large initial group formed by members with an intermediate level of diversity in the focus of their editing but having an equal and lower level of longevity.